2013
DOI: 10.1165/rcmb.2012-0442oc
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of gp91phox Inhibits Allergic Airway Inflammation

Abstract: Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, a multienzyme complex, is the major source for production of reactive oxygen species (ROS). ROS are increased in allergic diseases, such as asthma, but the role of ROS in disease pathogenesis remains uncertain. We hypothesized that mice unable to generate ROS via the NADPH oxidase pathway would have decreased allergic airway inflammation. To test this hypothesis, we studied gp91phox 2/2 mice in a model of allergic airway inflammation after sensitizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
1
19
0
1
Order By: Relevance
“…In the present study, one possible mechanism by which innate recruitment of neutrophils by pollens shifts the immune response to an allergic phenotype upon repeated challenge is induction of a state of sustained oxidative stress in the airways by repeated recruitment of activated ROS-generating neutrophils. This is suggested by reports that mice deficient in gp91phox, the dominant superoxide-generating enzyme in neutrophils, have decreased ROS generation and mount an attenuated allergic inflammatory response to allergen challenge (19). Additionally, chronic oxidative stress can worsen allergic asthma (21)(22)(23)(24), alter dendritic cell function, and modify the Th1/ Th2 balance (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, one possible mechanism by which innate recruitment of neutrophils by pollens shifts the immune response to an allergic phenotype upon repeated challenge is induction of a state of sustained oxidative stress in the airways by repeated recruitment of activated ROS-generating neutrophils. This is suggested by reports that mice deficient in gp91phox, the dominant superoxide-generating enzyme in neutrophils, have decreased ROS generation and mount an attenuated allergic inflammatory response to allergen challenge (19). Additionally, chronic oxidative stress can worsen allergic asthma (21)(22)(23)(24), alter dendritic cell function, and modify the Th1/ Th2 balance (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that lymphocytes from gp91 phoxϪ/Ϫ mice (deficient in the superoxide production that accompanies the respiratory burst) produce less IL-13 under allergic sensitization (54), indicating that IL-13 production is under ROS control and that antioxidants are able to (A) Analysis of the correlation between IL-13 serum amounts and hepatic hydroxyproline contents in infected nontreated or treated mice. Samples examined for hydroxyproline and IL-13 came from the same pool of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil are a major source of oxidative stress by their respiratory chain. Because mice deficient in gp91phox showed less Th2 cytokine secretion and allergic inflammation [37], recruitment of ROS-generating neutrophils after allergen challenge may have an important role in subsequent allergic inflammation. Several studies have shown that chronic oxidative stress can worsen allergic asthma [3841], alter DC function, and modify Th1/Th2 balance [42,43].…”
Section: Molecular Mechanisms By Which Neutrophils Shifts To An Allermentioning
confidence: 99%
“…Since neutrophils recruited by intranasal allergen challenge generates sustained ROS in the airways, it is likely that this property of neutrophil promotes allergic inflammation through ROS generation. This is suggested by reports that mice deficient in gp91phox, the dominant superoxide generating enzyme in neutrophils, have decreased ROS, and mount an attenuated allergic inflammatory response to allergen challenge [37]. LTB4 generation from recruited neutrophil to the skin stimulates accumulation of effector CD4 + T cells to OVA-challenged skin, thereby facilitating allergic skin inflammation [23].…”
Section: Molecular Mechanisms By Which Neutrophils Shifts To An Allermentioning
confidence: 99%